Y = -3X^2 - 6X + 4.
Vertex Form: y = a(x - h)^2 + k.
h = Xv = -b/2a = 6/-6 = -1.
Substitute -1 for x in the given Eq:
k = -3(-1)^2 - 6(-1) + 4=3 + 6 + 4 = 7.
V(h , k) = V(-1 , 7).
Vertex Form: y = -3(x + 1)^2 + 7.
Axis = h =Xv = -1.
The axis is a vertical line and equals
-1 for all values of y.
Let x = 0 and solve for y:
y = 3*0^2 - 6*0 + 4 = 4 = Y-Int.
The solutions,x-Intercepts, and roots
are all the same.
x = (6 +- sqrt(6^2 + 48)) / -6,
x = (6 +- sqrt(84)) / -6,
x = (6 +- 9.17) / -6,
x = (6 + 9.17) /-6 = - 2.5275.
x = (6 - 9.17) / -6 = 0.5275.
Solution set: x = -2.5275, x = 0.5275.
Give vertex, axis, x-intercepts and y-intercepts to parabola
y= -3x^2-6x+4
1 answer